The Contribution of Marketing Innovation in the Development of Competitive Advantage of Modern ‎Business Organizations: A Study of Sweetly Organization in Djelfa, Algeria‎ - khaled Gachi (Dirassat Journal Economic Issue, 2015)
In this research was the study of the contribution of marketing innovation in the development of competitive advantage for the organization sweetly in Djelfa, which were highlighted this role and its importance in achieving competitive advantage, as well as the Relationship between the Independent variables and the role of innovation with respect to the marketing test. With the adoption of descriptive analytical method was also applied a comprehensive Survey of all the original members of the society for the study of the heads of the interests and tires were distributed to 30 single. The study found a group of the most important results: -Found through analysis that innovation in the field of product through the organization sought to create new products or renewal of what is or doing research and development, increases the effectiveness of marketing activities Alokhry.kma results confirmed that the innovation in the product is the most effective elements in the organization replaced the study of the rest of the other elements. Has been reached to a set of recommendations based on the practical side, namely: The organizations conducting research in the field of market and customer needs and reconsider the current directions in order to create value for customers through product with high specifications and the right price. For the organization under study, they do not have their own marketing interest, in addition to the lack of specialized personnel in the field of marketing, which means there is no fundamental basis for the establishment of innovation marketing, both in the products or in any other field of marketing areas, so by separating the marketing tasks for interest trade and the establishment of special interest to marketing so that you can perform marketing activities effectively. As well as the establishment of a system of incentives and rewards special individuals who contribute to the innovative process in order to motivate their employees to innovate. Fund also Put ideas can all contribute to the organization workers, as every innovation begins with the idea.